EFEKTIVITAS BIMBINGAN KELOMPOK UNTUK ORIENTASI KARIR STUDI LANJUT SISWA DI SANGGAR BIMBINGAN KEPONG - Lubis, Maudi Alwani Akmal; M. Fauzi Hasibuan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine whether group counseling at the Kepong Guidance Center improves students' career orientation. Final-year students need to have a strong career orientation to prepare themselves for further education. Using a one-group pretest-posttest pre-experimental design, this study employed a quantitative methodology. The research population consisted of eight students—five from Grade V and three from Grade VI—who were all enrolled at the Kepong Guidance Center. Total sampling was the method used, meaning the research sample included the entire population. A validated career orientation scale was used as the research instrument. With a t-value of 4.372, which is greater than the critical t-table value of 2.365 at a 0.05 significance level, the results indicate a substantial increase in students' career orientation scores after the group counseling sessions. The average score increased from 65.25 to 82.75, reflecting a 26.8% improvement in the effectiveness of group counseling. It is evident that students at the Kepong Guidance Center benefit from group counseling in terms of their career orientation.